A Ternary Ni46Co40Fe14 Nanoalloy‐Based Oxygen Electrocatalyst for Highly Efficient Rechargeable Zinc–Air Batteries. Issue 46 (14th September 2018) - Nam, Gyutae; Son, Yeonguk; Park, Sung O; Jeon, Woo Cheol; Jang, Haeseong; Park, Joohyuk; Chae, Sujong; Yoo, Youngshin; Ryu, Jaechan; Kim, Min Gyu; Kwak, Sang Kyu; Cho, Jaephil
Abstract: Replacing noble‐metal‐based oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) electrocatalysts is the key to developing efficient Zn–air batteries (ZABs). Here, a homogeneous ternary Ni46 Co40 Fe14 nanoalloy with a size distribution of 30–60 nm dispersed in a carbon matrix (denoted as C@NCF‐900) as a highly efficient bifunctional electrocatalyst produced via supercritical reaction and subsequent heat treatment at 900 °C is reported. Among all the transition‐metal‐based electrocatalysts, the C@NCF‐900 exhibits the highest ORR performance in terms of half‐wave potential (0.93 V) in 0.1m KOH. Moreover, C@NCF‐900 exhibits negligible activity decay after 10 000 voltage cycles with minor reduction (0.006 V). In ZABs, C@NCF‐900 outperforms the mixture of Pt/C 20 wt% and IrO2, cycled over 100 h under 58% depth of discharge condition. Furthermore, density functional theory (DFT) calculations and in situ X‐ray absorption spectroscopy strongly support the active sites and site‐selective reaction as a plausible ORR/OER mechanism of C@NCF‐900. Abstract : A ternary Ni46 Co40 Fe14 nanoalloy with excellent performance in rechargeable Zn–air batteries is prepared by supercritical reaction and heat treatment. Both theoretical calculation and in situ X‐ray absorption spectroscopy (XAS) prove that the Ni46 Co40 Fe14 can have site‐selective adsorption during oxygen electrocatalytic activities due to the charge transfer between transition metals, which is thought to be responsible for the high oxygen reduction/evolution activity.